Efectividad de la terapia de aceptación y compromiso como tratamiento del trastorno de ansiedad social - Arellano Soriano, Sebastian Arturo (2024)
Acceptance and Commitment Therapy is a psychotherapeutic model that has gained great importance in the field of clinical psychology during the past decade, in the search for more effective options for the treatment of psychopathologies that are not responsive to traditional therapies, such as is the case of social anxiety disorder. For this reason, the goal of this paper was to identify the effectiveness of Acceptance and Commitment Therapy (ACT) in the treatment of social anxiety disorder (SAD), for people between the ages of 16 and 35. An exhaustive search was carried out in the SCOPUS database to identify scientific research that evaluated both variables. 10 studies that met the inclusion and exclusion criteria were chosen. The results showed that ACT is an effective treatment for social anxiety disorder, significantly reducing its usual symptoms, after applying the protocol in a variety of ways: individual therapy, group therapy, in-person therapy, online therapy, self-help books, virtual reality.